2018
DOI: 10.1590/s0100-204x2018000100001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro infectivity of Spodoptera frugiperda multiple nucleopolyhedrovirus to different insect cell lines

Abstract: The objective of this work was to evaluate the response of an in vitro host range to Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV), a pathogenic virus to the fall armyworm (Spodoptera frugiperda, Lepidoptera: Noctuidae), for the further development of a biopesticide based on cell culture systems. The cell lines from Bombyx mori (BM-5), Lymantria dispar (IPLB-LD-625Y), Trichoplusia ni (BTI-Tn-5B1-4), Anticarsia gemmatalis (UFL-AG-286), and S. frugiperda (IPLB-SF-21AE and Sf9) were tested for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…There are several studies focused on the bioreactor culture of baculoviruses aiming to achieve recombinant protein production [ 26 , 27 , 28 , 29 ], although only a few studies have been conducted regarding the in vitro production of baculoviruses for pest control [ 30 , 31 , 32 ]. Advances were achieved in the selection of suitable cell lines for high OBs production [ 15 , 33 ]. However, there are still challenges to be overcome in the scale-up process for large-scale in vitro production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies focused on the bioreactor culture of baculoviruses aiming to achieve recombinant protein production [ 26 , 27 , 28 , 29 ], although only a few studies have been conducted regarding the in vitro production of baculoviruses for pest control [ 30 , 31 , 32 ]. Advances were achieved in the selection of suitable cell lines for high OBs production [ 15 , 33 ]. However, there are still challenges to be overcome in the scale-up process for large-scale in vitro production.…”
Section: Discussionmentioning
confidence: 99%
“…(CVI code BRM5023). The virus stock suspension of 4.65 × 10 6 pfu/mL was previously obtained from static culture [ 15 ]. All cell cultures used Sf-900™ III Serum Free Medium (Gibco, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a major concern of this technology is the mutation of the isolates since several passages in insect cell cultures might lead to deletions in some parts of the genome, which might render the isolates less virulent [32,64,76] or even loss of oral infectivity [114]. Nonetheless, ongoing studies on the optimization of the production of baculovirus OBs in cell culture [158][159][160] showed that the propagation of SfMNPV in Sf9 and Sf21 cells in both static and suspension cultures results in a higher OB production in comparison to other cell types [159,160]. Further optimization of in vitro production in cell culture might lead to a successful commercial mass production.…”
Section: Challenges Of Using Baculoviruses For Biological Controlmentioning
confidence: 99%